The Effect of E-Service Quality on Student Satisfaction At Jakarta State Polytechnic in Using Academic Information Systems - Syamsurizal Syamsurizal; Aulia Nur Cahyanti; Erwin Permana (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the influence of electronic service quality (e-service quality) on student satisfaction in using the KubacaPNJ application as a digital literacy platform at Politeknik Negeri Jakarta. The research employs a descriptive approach by analyzing user reviews on the Google Play Store platform. The results show that the KubacaPNJ application has generally been able to provide adequate services in supporting students' literacy needs, particularly in terms of system accessibility, availability of digital book features, and user data protection through account authentication mechanisms. Based on the analysis of user reviews, approximately 60% of users provided positive feedback, 27% gave negative feedback, and 13% did not provide any rating. These findings indicate that electronic service quality influences the level of student satisfaction, where the better the quality of electronic services provided by the system, the higher the level of student satisfaction in utilizing the digital service. Therefore, application developers are recommended to continuously improve service quality, particularly by minimizing bugs and errors, improving the clarity of system navigation, and enhancing the transparency of application information to ensure a more optimal user experience.